2022
DOI: 10.3389/fimmu.2022.813979
|View full text |Cite
|
Sign up to set email alerts
|

ALKBH5-Mediated m6A Modification of A20 Regulates Microglia Polarization in Diabetic Retinopathy

Abstract: BackgroundTo investigate the role of microglia polarization in the pathogenesis of diabetic retinopathy, and study the mechanism of ALKBH5-mediated m6A modification of A20 of retinal microglia polarization.MethodsDiabetics rats were constructed and the M1/M2 polarization of retinal microglia was determined using immunofluorescence, flow cytometry, and quantitative real-time PCR (qRT-PCR). Glucose at different concentrations was added to treat the microglia, and the polarization rate was detected. RNA sequencin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 43 publications
0
21
0
Order By: Relevance
“…It has been shown that the dysfunctional demethylation of ALKBH could reduce the production of in ammatory factors in ARDS (71). In diabetic retinopathy, the change of ALKBH5 expression could cause m6A modi cation to be dysfunctional (72). In cancers, it was shown that ALKBH5 and its related genes were enriched in the in ammatory, metabolic, and immune signaling pathways in gliomas, suggesting that ALKBH5 might be a potential treatment for this disease (73).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the dysfunctional demethylation of ALKBH could reduce the production of in ammatory factors in ARDS (71). In diabetic retinopathy, the change of ALKBH5 expression could cause m6A modi cation to be dysfunctional (72). In cancers, it was shown that ALKBH5 and its related genes were enriched in the in ammatory, metabolic, and immune signaling pathways in gliomas, suggesting that ALKBH5 might be a potential treatment for this disease (73).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a higher rate of M1 inflammatory type but lower rate of M2 anti-inflammatory type were observed in both diabetic rats and BV2 cells (a type of mouse microglia cell line) treated with glucose (213). High glucose repressed expression of Alkbh5 in microglia, which in turn contributed to lower A20 (also known as tumor necrosis factor-a induced protein 3 (TNFAIP3)) expression and increased M1 polarization; these changes were the results of higher m 6 A modification level and faster degradation rate of A20 mRNA, which ultimately contributed to the initiation and development of DR (213). Overall, epigenetic regulation of these targets may help control and delay the development and progression of DR, which provides new insights into the pathogenesis and therapy of this disease.…”
Section: The Role Of Epitranscriptomics In Diabetic Retinopathymentioning
confidence: 99%
“…Dysregulation of microglia (tissue-specific macrophages in the retina) polarization was considered to be one of the primary pathogenesis of DR (211,212). Indeed, a higher rate of M1 inflammatory type but lower rate of M2 anti-inflammatory type were observed in both diabetic rats and BV2 cells (a type of mouse microglia cell line) treated with glucose (213). High glucose repressed expression of Alkbh5 in microglia, which in turn contributed to lower A20 (also known as tumor necrosis factor-a induced protein 3 (TNFAIP3)) expression and increased M1 polarization; these changes were the results of higher m 6 A modification level and faster degradation rate of A20 mRNA, which ultimately contributed to the initiation and development of DR (213).…”
Section: The Role Of Epitranscriptomics In Diabetic Retinopathymentioning
confidence: 99%
“…Therefore, reducing the polarization of M1 glial cells or driving their conversion to the anti-inflammatory M2 phenotype can aid nerve recovery and lessen secondary damage (Liu W. et al, 2020). According to recent studies, m6A modification plays a critical role in glial phagocytosis and polarization (Figure 2; Li et al, 2021;Zhou et al, 2021;Chen et al, 2022). A study on uveitis found that deletion of the m6A reader YTHDC1 enhances the M1 polarization of microglia and accelerates inflammation (Zhou et al, 2021).…”
Section: Future Directions Related To the Role Of N6-methyladenosine ...mentioning
confidence: 99%